Barriers to Adoption of Office‐Based Laryngeal Surgery. (2nd September 2014) - Verma, Sunil P.; Merati, Albert L.
Abstract : Objectives: Office‐based laryngeal surgery (OBLS) has been shown to be safe and efficacious for many common laryngeal disorders. Despite this, OBLS is not widely adopted by otolaryngologists. This study investigated what barriers exist to OBLS through a survey of practicing otolaryngologists. Methods: A questionnaire was sent to the membership of the Academy of Otolaryngology—Head and Neck Surgery in winter 2013. Results: A total of 173 otolaryngologists completed the survey. The availability of lasers for OBLS was cited as a major obstacle by 119 out of 173 (75%) of respondents. Reimbursement of disposables and lack of CPT codes for OBLS were the second and third major obstacles noted, respectively (85/173 [53%] and 68/173 [43%]). Reliability of results in the office was less commonly cited as a major obstacle by 24 out of 173 (15%) of respondents. Conclusions: Organizational and financial considerations continue to be barriers for adoption of OBLS.